Enhancement techniques on a multistage solar distiller - Ang, Jia Yi (2022)
A solar distiller is able to provide clean water to be used in rural areas especially in the poor countries where the people there are hard to access to clean water supply. The water productivity of a solar distiller is strongly reliant on solar radiation, therefore a traditional solar is still unable to deliver sufficient volumes of clean water. Therefore, this research studied an enhanced multi-stage solar distiller designed with corrugated condensation surfaces, and parafin wax as phase change material (PCM) added in each stage. In this research, experiments with different multi-stage solar distiller models have been conducted on four different ways of operation. The first way is a multistage solar distiller with flat condendation surface without using PCM. The second way is a multi-stage solar distiller with flat condendation surface with PCM inside every stage. Third is a multi-stage solar distiller with corrugated condendation surface without PCM. Fourth is a multi-stage solar distiller with corrugated condensation surface with PCM. The corresponding fresh water productivity obtained in the result was 0.2031 kg/day, 0.2741 kg/day, 0.3492 kg/day, and 0.4391 kg/day respectively. Whereas, the corresponding cost of clean water per kilogram was RM 1.33/kg, RM 1.03/kg, RM 0.79/kg, and RM 0.66/kg respectively. All experiments were conducted at Cheras, Selangor at the days of 21 March 2022, 22 March 2022, 23 March 2022, and 24 March 2022. The hourly solar irradiance for each experiment and the temperature of condensation surface and water at every stage were measured. The contribution for the study is the ability to provide unlimited supply of clean water in bigger amount in the poor countries by using the designated enhanced multi-stage solar distiller. It was concluded that the fresh water productivity greatly increased in a multi-stage solar distiller integrated with PCM and corrugated condensation surfaces.